Digital Entrepreneurship: Opening Opportunities, Highlighting Challenges, and Mapping Start-Up in Palembang, Indonesia - Azwardi Azwardi; Sri Andaiyani; Alghifari Mahdi Igamo (AIBPM Publisher, 2022)
This study specifically aims to analyze the opportunities, challenges, and mapping of Startups in Palembang. The object of this research is divided into two, namely founders and digital consumers. The method used in this research is a Mixed method, combining quantitative research methods and qualitative. Data was collected by distributing questionnaires to founders and digital consumers in Palembang. The study found that there were 40 start-ups in Palembang, but only 16 are active. Many start-ups in Palembang are engaged in the service sector. Opportunities for products and services for local start-ups in Palembang are as follows: (a). From the founder's point of view, they already have a workforce that is quite capable, high enthusiasm, creativity, and quality to innovation; (b) From the user side, the generation that is more interested in technological advancements and internet use is Generation Z; (c) From the non-users side, those who have not enjoyed the products and services offered by local start-ups in Palembang do not know for sure the existence of start-ups. The challenges in the form of obstacles that must be resolved by start-ups are as follows: (a) from the founder's perspective, the digital business sector that is occupied by the majority is in the form of general commodities, especially in the service sector. They have obstacles in the form of capital assistance and support, facilities, clarity of regulations and laws from the government; (b) from the side of start-up users, the products and services offered have attracted the attention of users from Generation Z.